Lychee (Litchi chinensis Sonn.) peel flour: effects on hepatoprotection and dyslipidemia induced by a hypercholesterolemic diet - ESTELA R. QUEIROZ (Anais da Academia Brasileira de Ciências, 2017)
ABSTRACT Dyslipidemias are associated with the incidence of cardiovascular diseases, obesity, diabetes, hypertension and hepatic steatosis, being the cause of morbidity and mortality. This study investigated the effects of lychee peel flour (PF) on serum levels of total cholesterol (TC), low-density lipoprotein (LDL-c), triacylglycerols (TAG) and various parameters related to obesity, in rats fed a hypercholesterolemic diet. Therefore, 20 male rats were used. In the first 21 days, the animals were fed a hypercholesterolemic diet, except for control group. In the following 21 days, their diets were modified, and they received a standard diet (Control); hypercholesterolemic (Hyper); hypercholesterolemic + 5% PF (PF5) and hypercholesterolemic + 10% PF (PF10). The results revealed that PF intake attenuated weight gain, reduced body mass index, glucose and the levels of TAG, TC, LDL-c, hepatic enzymes and leptin, besides the percentage of hepatic lipids, liver lipid peroxidation and frequency of severe steatosis. Histological studies of the aorta did not show the formation of the atheromatous plaque. These results reinforce its potential to reduce the risk of diseases associated with obesity.